Interferometric grazing incidence test of rough steep convex spherical and aspherical surfaces: First simulations and experimental proof of principle - Rothau, Sergey; Lindlein, Norbert; Schwider, Johannes (Applied Optics, 2019)
In the past, grazing incidence interferometry has been applied for rough plane, cylindrical, acylindrical, and general rod-like surfaces using diffractive beam splitters. Here, we demonstrate that also rough convex steep rotational symmetric spherical or aspherical surfaces can be measured along one meridian in a single step using diffractive beam splitters and phase-shifting techniques. The extension to the whole surface can be attained by successive meridional measurements of the surface under test by azimuthal adjustments. The principle of the method is given and for a spherical ball lens as an extremely curved surface simulated, and experimental data are presented. The features of the interferogram are discussed, and the experimental evaluation of a single meridian including the unwrapped phase data is shown.
CRIS-Team Scopus Importer:2019-11-29